Pengaruh PDB, Nilai Tukar, Inflasi, dan Kondisi Geopolitik Terhadap Neraca Perdagangan BRICS - Desty Nuraini; Thomas Adrian; Rizka Malia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of Gross Domestic Product (GDP), exchange rate, inflation, and geopolitical conditions on the trade balance of BRICS countries during the 2015–2024 period. The research employs a panel data regression method using the Fixed effext Model (FEM). The data were collected from various relevant international sources and analyzed using statistical software. The results indicate that the exchange rate and geopolitical conditions have a significant effect on the trade balance of BRICS countries. Meanwhile, GDP and inflation do not have a significant effect on the trade balance. Simultaneously, GDP, exchange rate, inflation, and geopolitical conditions significantly influence the trade balance. These findings suggest that external factors, particularly exchange rates and geopolitical conditions, play a more important role in determining the trade balance of BRICS countries than domestic factors such as GDP and inflation. Therefore, maintaining exchange rate stability and enhancing the ability to respond to global geopolitical dynamics are essential for sustaining the international trade performance of BRICS countries.